Basic Profile of Child Marriage in Mozambique - Male, Chata; Wodon, Quentin (World Bank, Washington, DC, 2016)
Measures of child marriage are high in Mozambique. The share of women ages 18-22 who married as children is 51.5 percent and it has increased over time. However the share of women marrying very early, before the age of 15, has declined, but not rapidly. Child marriage is associated with lower wealth, lower education levels, and higher labor force participation. These are however only correlations, not necessarily causal effects. In order to design programs and policies to reduce child marriage, information is needed on the trend in the practice over time, where it is most prevalent in a country, and what the characteristics of girls marrying early are.